Antimicrobial and Anticancer Activities of Lactiplantibacillus plantarum Probio87 Isolated from Human Breast Milk - Pei, Xu; Mageswaran Uma, Mageswary; Azka Ainun, Nisaa; Xiang, Li; Yi Jer, Tan; Chern Ein, Oon; Cheng Siang, Tan; Wen, Lo; Min Tze, Liong (MDPI, 2025)
Background/Objectives: This study evaluated the in vitro probiotic potential of Lactiplantibacillus plantarum Probio87 (Probio87), focusing on its physiological robustness, safety, antimicrobial properties, and anticancer activity, with relevance to vaginal and cervical health. Methods: Tests included acid and bile salt tolerance, mucin adhesion, and carbohydrate utilization. Prebiotic preferences were assessed using FOS, GOS, and inulin. Antibiotic susceptibility was evaluated per EFSA standards. Antimicrobial activity of the cell-free supernatant (CFS) was tested against Staphylococcus aureus, Escherichia coli, and Candida species. Effects on Lactobacillus iners and L. crispatus were analyzed. Anticancer properties were assessed in HeLa, CaSki (HPV-positive), and C-33A (HPV-negative) cervical cancer cell lines through proliferation, apoptosis, angiogenesis, and cell cycle assays. Results: Probio87 showed strong acid and bile tolerance, efficient mucin adhesion, and broad carbohydrate utilization, favoring short-chain prebiotics like FOS and GOS over inulin. It met EFSA antibiotic safety standards. The CFS exhibited potent antimicrobial activity, including complete inhibition of Candida albicans. Probio87 selectively inhibited L. iners without affecting L. crispatus, indicating positive modulation of vaginal microbiota. In cervical cancer cells, the CFS significantly reduced proliferation and angiogenesis markers (p < 0.05), and induced apoptosis and cell cycle arrest in HPV-positive cells, with minimal effects on HPV-negative C-33A cells. Conclusions: Probio87 demonstrates strong probiotic potential, with safe, selective antimicrobial and anticancer effects. Its ability to modulate key microbial and cancer-related pathways supports its application in functional foods or therapeutic strategies for vaginal and cervical health.